General Introduction to the Role of the Library for University Education - Virkus, Sirje; Metsar, Silvi (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
Our society is undergoing a process of rapid change, moving toward what is called the information society, the knowledge society, the network society or the informational mode of development (Castells, 1996; Inglis et al, 2002: 17) refer to the following features of the current period: dynamic and continuous change and transformation; the failure of great theories such as Marxism to locate and predict directions of change; the discontinuous and erratic rather than evolutionary nature of social change; the juxtaposition of various images of social, economic and political life and the transformation of images like Disney world, TV sports and Web pages into the realities with which we deal. It is believed that information and knowledge are distinguishing features of this modern society and the main driver of this change is the growing use of information and communication technologies (ICT).